حدود وضوابط ممارسة الإضراب في الوظيفة العمومية - خديجة أوذينة – حسناء أوذينة (جامعة المسيلة, 2022)
يتناول هذا البحثُ فصلين مهمّينِ في مجالاتِ القانون، هما محور الحقوق والحريات الأساسية، والمتمثّلة في الحدود القانونية لممارسة الموظف لِحقِّ الإضراب في الوظيفة العمومية؛ يقابلُه في الفصل الثاني ضوابطُ ممارسةِ هذا الحقّ. وهذه المرافق تقوم على مبادئَ أساسية، أهمُّها مبدأُ سيرِ المرفق العامّ بانتظام، لكن ممارسة هذا الحقّ يتعارض ويصطدم مع هذا المبدأ، وتنتج عنه آثارٌ خطيرةٌ ذاتُ حدّةٍ وجسامةٍ كبيرتين. في الجزائر، تمّت وِلادةُ حقِّ الإضراب، بعد تطوراتٍ سياسيةٍ هامّة شهدتها البلاد، من تعنُّتِ الدّولة وتسلٌّطِها، لتستحقَّ بكلِّ جدارةٍ هذا الوسامَ بصدور دستور 1989، الذي اعترفَ بحقِّ الإضراب في القطاعين العامّ والخاصّ. وتأكيدًا لذلك أصدر المشرِّعُ القانون رقم 90/02، المعدّل والمتمَّم بالقانون رقم 91/27، المتعلِّق بالوقاية من النزاعاتِ الاجتماعية في العمل وتسويتِها وممارسةِ حقِّ الإضراب. وقد تناولنا في هذا البحث النّهجَ الذي اعتمدهُ المشرِّعُ في تحديدِ ضوابطِ ممارسةِ حقِّ الإضراب للتّقليلِ من حِدّةِ آثارهِ الخطيرة على سيرِ المرافق العامّة. Abstract This research contains two important chapters from the fields of law, the axis of basic rights and freedoms, which consist of the limits of the exercise of the right to strike in the public office. In the second chapter, we discuss the controls for exercising this right. These services are based on basic principles, the most important of them is the principle of the regular functioning of the public service, but the exercise of this right conflicts with this principle, and results in dangerous effects. In Algeria, the right to strike was born after important political developments in the country with the issuance of the 1989 constitution, which recognized the right to strike in the public and private sectors. Accordingly, the legislator issued Law No. 90/02 amending and supplementing by the Law No. 27/91 related to the prevention and settlement of social conflicts at work and the exercise of the right to strike. In this research, we dealt with the approach adopted by the legislator in determining the controls and exercising the right to strike in order to reduce the severity of its dangerous effects on the functioning of public service.
Keywords: الاضراب -الوظيفة العمومية -